Politeness Principle in H.G. Well’s Novel “The War of the Worlds” - Dinda Sari; Dahlia D. Moelier; Sudirman Maca (Fakultas Sastra, Universitas Bosowa, 2021)
This Study aims to identify the type of politeness principle used by the character in the novel and to find out how the politeness principle that was used by the characters in the novel. The data source of the study is the novels In H.G Well’s The War of The World. In analyzing the data, the researcher used qualitative descriptive method and Maxim’s theory. Data were obtained by using the techniques of reading and analyzing. In this study, researcher found 19 data using 6 types of leech theory, namely tact maxim, modesty maxim, approbation maxim, agreement maxim, sympathy maxim, and generosity maxim. In using tact maxim the characters express it in a sincere way, in using modesty Maxim the characters used it by reducing self-praise, in using approbation maxim characters use it in a polite way of praising someone. The agreement maxim used by the characters for asking permission and agreeing, while sympathy maxim used by characters to to keep the people feeling, and generosity maxim for praising someone.